MENINGKATKAN KEMAMPUAN KOSAKATA BAHASA INGGRIS TERHADAP TENAGA PENGAJAR MELALUI APLIKASI DUOLINGO - Erfak Glen Ridho Kaligis; Lucky Purwantini; Rima Rikmasari (Universitas Islam 45 Bekasi, 2022)
Human resources are the driving force of a country to develop forward and prosper. In this modern era, there has been a lot of competition everywhere that demands highly skilled and competent resources. Thus, teachers as instruments for producing quality resources must have the ability and expertise to maintain the quality of these resources. Of all the specific skills and expertise, English is one of the important components of Indonesian teachers, but in fact, many teachers in rural areas have poor English skills that could threaten the quality of their students. The lack of materials and facilities required causes poor English language skills for local teachers in Madrasah Ibtidaiyah Matla'ul Anwar 4. Furthermore, they have not received adequate education regarding English especially, Vocabulary. Seeing this problem, the application of learning using media application Duolingo can improve the vocabulary skills of Madrasah Ibtidaiyah Matla'ul Anwar 4 teachers in Segar Tanjung Hamlet, Segaran Village, Batujaya District, Karawang Regency. The method used is face-to-face training at school and using a smartphone from the teacher or the trainer himself which is attended by 3 to 4 teaching staff. Teachers will be trained and taught about learning media and Duolingo to improve their vocabulary as well as a learning tool using smartphones and laptops. The results obtained were very positive, the teaching staff had understood the function and use of vocabulary and its definitions. They are also considering using learning media, such as Duolingo, into their English lessons at school.